35 Right Heart (RH) 2D-Strain Analysis may help to Identify Left Ventricular Assist Device (LVAD) Cadidates at Risk of Developing Postoperative RV Failure. (6th June 2015) - Charisopoulou, Dafni; Banner, Nicholas; Andre, Simon; Rahman-Haley, Shelley
Abstract : Purpose: Right Ventricular Failure (RVF) after LVAD implantation is associated with increased morbidity and mortality. We analyse right (RH) mechanics by 2D echo, strain and haemodynamic indices in an effort to define patters which may predispose to RVF during LVAD support. Methods: 70 LV failure patients (47 ± 12 yrs, 59 male, ischaemic: 21%, LV EF: 23%±10) received continuous-flow LVAD as bridge to transplantation within 18 months. Patients were divided into those who developed RVF during LVAD therapy (RVF group) and those who did not (non-RVF). We compared haemodynamic, echo and strain data between the groups. Results: 21 patients (30%) developed post-LVAD implantation RVF resulting in lower survival duration (RVF: 372 days ± 345 vs 650 ± 369, p = 0.03), while 14 patients of the RVF group required subsequent right VAD support. There were no significant differences in age, sex, HR or rhythm, LVEF, cardiac index or in RV stroke work index, mean or systolic pulmonary artery pressure, pulmonary vascular resistance index, TAPSE, RV fractional change area, tricuspid regurgitation grade or TDI systolic and diastolic parameters (p > 0.2). However, RVF group had higher RV end-diastolic pressure (RVEDP, 25 ± 7 mmHg vs 15 ± 6, p = 0.02) and higher mean RA pressure (mRAP, 25 ± 6 mmHg vs 15 ± 7, p = 0.03). Additionaly, there was lower RA peak strain (RAPS: 11 ± 1 vs 33 ± 8%, p = 0.01), lower and later-occurring RV global peak strain (RVGS: 8 ± 2.8% vs 9.2 ± 2.5, p = 0.03, time to RVGS: 57% ±10 vs 47 ± 17, p = 0.03), lower and later-occurring RV free wall peak strain (RVFWS: 8.6 ± 2.7% vs 14.8 ± 2.9, p = 0.01, time to RVFWS: 56% ±19 vs 45 ± 17, p = 0.04), lowerRVFW peak systolic strain rate (RVFWSR: 0.94 ± 0.47s-1 vs 1.1 ± 0.3, p = 0.05) occurring earlier in systole (17% ± 10 vs 0.29 ± 0.13, p = 0.04) and higher late RVFW diastolic strain rate (0.43 ± 0, 2s-1 vs 0.28 ± 0.21, p = 0.01). RV contraction after PV closure was more frequently seen in the RVF group (30% vs 20%, p = 0.03). There was also greater time delay between RVFW and septal peak strain (RVD, 147 ± 52 ms vs 53 ± 38, p = 0.03) and between RVFWS and LVFWS (136 ± 55 vs 78 ± 40 ms, p = 0.03). LV strain indices were similar for both groups. Independent predictors of RVF were higher mRAP (OR: 6, 95% CI:0.686–0.976, p = 0.03), lower RAPS (OR: 1.2, CI:1.083–1.716, p = 0.003), lower RVFWS (OR: 1.4, CI: 1.012–2.347, p = 0.04) and greater RVD (OR: 1.028, CI:1.008–1.034, p = 0.01). Higher predictive value was shown for RVD (AUC:0.84), mRAP (AUC: 0.82) and RAPS (AUC: 0.795) Conclusion: LVAD recipients, who developed post-operative RVF, exhibited lower RAPS and RVFWS and greater RVD, indicating decreased RH compliance and dyssynchronous RV function. RH strain analysis may add incremental value to 2D echo assessment of LVAD candidates and improve decision making before VAD implantation.